7,8-Dihydroxyflavone Protects Nigrostriatal Dopaminergic Neurons from Rotenone-Induced Neurotoxicity in Rodents - Shuke Nie; Kai Ma; Mingkuan Sun; Matthew Lee; Yang Tan; Guiqin Chen; Zhentao Zhang; Zhaohui Zhang; Xuebing Cao (Parkinson's Disease)
7,8-Dihydroxyflavone (7,8-DHF) is thought to be a promising therapeutic agent for various neurodegenerative diseases. The major purpose of this study was to investigate the neuroprotective effects of 7,8-DHF on the rotenone-induced motor deficit of Parkinson’s disease. Nine-month-old rats were treated with rotenone (2 mg/kg/day, i.h.) for 5 weeks to establish the animal model of Parkinson’s disease (PD), and 7,8-DHF (5 mg/kg, i.p.) was administrated daily throughout the whole period of rotenone injection. Five weeks later, an open field test was used to assess the motor ability of the animals. TH immunostaining was performed to evaluate rotenone-induced neurotoxicity on substantia nigra (SN) dopaminergic neurons and the DA terminals in the striatum. Western blot analyses were used to examine the expressions of TH, BDNF/TrkB signaling cascades, phospho-α-synuclein (Ser129), α-synuclein, and phospho-tau (Ser396) in SN. The results revealed that treatment with 7,8-DHF improved PD model’s behavioral performance and reduced dopaminergic neuron loss in the SN and striatum, associated with the activation of TrkB receptors and its signaling cascades, and reduced p-MAPK, p-α-synuclein, and p-tau. Collectively, these results indicated that 7,8-DHF displayed prominent neuroprotective properties, providing a promising therapeutic strategy for PD treatment.